Morphological and biochemical changes in response to salinity in sunflower (Helianthus annus L.) cultivars - Taher, Mehdi; Beyaz, Ramazan; Javani, Marieh; Gürsoy, Mehtap; Yildiz, Mustafa (Italian Journal of Agronomy, 2018)
This study was conducted to evaluate the alterations of some morphological and biochemical parameters of sunflower cultivars (‘08-TR-003’, ‘TR-3080’ and ‘TARSAN-1018’) under salt stress. For this aim, the seedling of sunflower cultivars was irrigated with tap water as a control, and with salinised water with 50, 150 and 250 mM NaCl for 30 days under controlled conditions. Salinity caused an apparent reduction in morphological parameters (plant height, leaf area, fresh weight, dry matter and water content) in all cultivars. Salt stress significantly (P<0.01) reduced the activity of glutathione reductase (GR) and ascorbate peroxidase (APX) activities in all sunflower cultivars expect for superoxide dismutase (SOD) activity. According to our results, SOD seems to play a key role in the antioxidative process in salt treated sunflower plants. Proline and malondialdehyde contents were significantly (P<0.05) increased under salt stress in all cultivars. Among the cultivars, ‘TR-3080’ had greater values in terms of morphological (plant height, leaf area, fresh weight, water content) and biochemical [GR, APX and SOD (secondly) activities and proline contents] parameters. In the light of these findings, cv. ‘TR-3080’ seems to be less affected by salt stress.